Detection of Fruit Meals Within Laboratory-Raised and Field-Trapped Adult Drosophila suzukii (Diptera: Drosophilidae) Guts - Kraft, Laura J.; Sit, Tim L.; Diepenbrock, Lauren M.; Ashrafi, Hamid; Aryal, Rishi; Fernandez, Gina E.; Burrack, Hannah J. (Frontiers in Ecology and Evolution, 2021)
The feeding habits of adult Brachycera are understudied and may provide important context for understanding invasive pest biology, as with the polyphagous small fruit pest Drosophila suzukii. We developed molecular methods to study adult D. suzukii gut content in order to understand its feeding habits. We designed and verified two primer pairs specific for either blueberries or blackberries and used a qPCR melt curve analysis to determine whether we can detect the presence or absence of berry feeding by adult flies. In a laboratory assay, the blueberry fly meal DNA can be detected for longer periods than the blackberry meal DNA. Generally, female gut contents are less variable than male gut contents. We also tested recently emerged flies that were not fed as adults but developed as larvae in either blueberries or blackberries. Some adult flies from each fruit had detectable fruit DNA in their gut, which could be due to pupal meconium feeding after emergence. Next, we aimed to test the primers in the field to develop techniques to track fruit feeding by D. suzukii in its natural field environment. First, to identify the most appropriate collection method, we determined how long we could detect fruit DNA, using previously developed primers within D. suzukii gut preserved in four types of trap fluid in the laboratory. The likelihood of detecting blackberry DNA differed by day, trap fluid, and between sexes. For the blueberry primer, the possibility of detecting blueberry DNA differed by trap fluid only. Based on those results, we used RV antifreeze with a Scentry SWD lure in field trials at two research station locations, one containing blackberries and one with blueberries. We established transects away from each fruit planting and collected up to 120 total flies at each point along transects. There were no significant differences in the number of flies containing berry DNA among collection points along the transect in both locations. These results suggest that adult flies move between crop and non-crop habitats and may not be highly dependent on fruit food resources.